Influence of Product, Price, Promotion and Place on Banana Market Trend in Kilimanjaro-Tanzania - Steven Tumaini; Raphael Gwahula; Salvio Macha (European Scientific Journal, ESJ, 2024)
The study focuses on the Product, Price, Promotion and Place On Banana Market Trend In Kilimanjaro, it provides the market strategy to enhance the competitiveness of banana companies in the current market dynamics. Through quantitative research, this paper revealed the effectiveness of (4P) in the Banana marketing strategy and the significant links between place, price, products, promotion and the impact in increasing the market opportunity in the banana sector. Specifically, the study evaluates the performance of marketing strategy practices across various dimensions. Marketing mix strategy were explored in terms of Product, Price, Promotion and Place. In addition, the data was collected from 575 banana growers throughout 52 wards. This study employed a cross-sectional survey approach to examine the commercial viability of the banana value chain, and the corresponding questionnaires were successfully collected. The results show (99.3%) of banana growers have a great challenge with access to the market and poor price information. Moreover, the producers (62.8%) rely on the middlemen rather than delivering bananas to the Private Banana Company. Based on these findings; for the farmers and private sector to generate growth and excellence, Private Banana Company need to decentralize their business model and develop a marketing strategy by implementing its marketing mix in a way that will acquire and then sustain its competitive edge in the market. These will enhance the competitiveness of banana companies and lay a solid foundation for their sustainable success in the banana business.